Motivación laboral y su relación con la satisfacción laboral en colaboradores del servicio de emergencia del Hospital III Iquitos de EsSalud año 2023 - Quispe Peñaloza, Nadine Yvonne (2025)
The general objective of this study is to determine how the relationship between work motivation and job satisfaction is presented in the collaborators of the emergency service of the III Iquitos hospital of ESSALUD in 2023, for them a non-experimental investigation of a correlational level was developed with a statistical sample of 69 collaborators, and a data collection instrument with a statistical reliability coefficient of 0.924 on 32 elements, the dimensions of self realization, task completion, work incentive, work environment, work benefits, development opportunities, conditions were addressed. work and tasks and responsibilities, within the main descriptive results on work motivation it is obtained that a mostly positive trend is presented, highlighting high levels of motivation to improve at work (61%), professional growth (58%), and satisfaction with the development of their work (54%), although a positive perception is observed in aspects such as the contribution to the institutional vision (72%) and equity among collaborators (55%), areas of opportunity are identified, such as the perception of training (22%) and economic recognition (10% and 13%), in terms of job satisfaction, employees show a generally positive perception, highlighting salary adequacy (41%) and the ability to cover economic needs (38%), Satisfaction is evident in aspects such as the financial contribution to training (52%) and professional growth opportunities (54%), however, areas for improvement are identified, such as additional economic incentives (48%) and job promotion processes ( 39%), in addition, the achievable challenge of the workplace (29%) and the variability at work (28%) stand out. The study concludes that a significant and positive relationship is evident between work motivation and job satisfaction, in addition that an increase in motivation levels is positively linked to a higher degree of job satisfaction at the participating institution.